PERANAN POLISI LALU LINTAS DALAM PENINGKATAN DISIPLIN BERLALU LINTAS DI WILAYAH HUKUM POLRES BOGOR - Saputra, Dedik; A.M., Komari; Gilalo, J. Jopie (DERECHTSSTAAT, 2016)
This study aims to determine the role of traffic police know the increase in traffic discipline and to know the police efforts to improve traffic discipline. The writing is done using the method of juridical sociological approach, the court concluded that the data obtained from an answer. This type of research used in the study of law is that legal research is descriptive. The results obtained that the role of the police carrying out of order and law enforcement in the field of traffic is by doing the demolition of highway users. The role of traffic police in improving the discipline and enforcement of traffic laws in Police Jurisdiction Police Bogor by the dissemination of traffic rules. The area is usually only seen one or two officers, more visible police officers assisted school children (MCC), Police Friends of Children (PSA), Satpol PP, Transportation Agency, the military and others. As a result the location of the normally chaotic start neat. Public transportation that generally take the path carelessly began to follow the sign that rules have been determined, including stops behind the road markings. Socialization is aimed at people. With the hope of growing awareness of the importance of order and lintas.Tak than mere appeals, undisciplined road users will be immediately ticketed. Range of efforts made to suppress the Bogor Police traffic policeman level of traffic violations is put tape shock, making the road median, make a zebra crossing, putting personnel at vulnerable places, and patrolling the road. When road users do not comply with rules set then the action will be penalized with a verbal reprimand and prosecution by giving a speeding ticket. Bogor Police traffic policeman in reducing offenses involving police discipline is the Friends of Children (PSA) for kindergarten children, coaching on a motorcycle taxi driver, extension to the applicants drivers license, do some police operations.